Young, Black/African American, and Latino communities are left behind despite legislative efforts in California to reduce HIV/STI disparities - Gaines, Tommi L.; Werb, Dan; Harris, Orlando (Frontiers in reproductive health, 2023)
Sexually transmitted infections (STI) have been on the rise in the United States with racial/ethnic minority groups, gay and bisexual men, and youth experiencing the highest STI and HIV infection rates. In 2022, California became the first state in the nation to pass legislation, Senate Bill 306 (SB 306), requiring health care plans to cover the costs of home test kits for STIs, including HIV. This study examines provisions within SB 306 and its potential to reduce STI and HIV disparities among key demographic groups and geographic regions within California. Ecological cross-sectional study involving 58 California counties. Descriptive statistics and choropleth maps compared HIV/STI prevalence rates, uninsured rates, demographic composition, and healthcare provider coverage across California counties. Three geographically weighted Poisson regression analyses were conducted to separately examine the association between proportion of uninsured and HIV, gonorrhea, and chlamydia prevalence rates. HIV/STI rates were significantly and positively associated with the proportion of uninsured residents in Central and Southern California counties. These counties had a higher proportion of demographic groups vulnerable to HIV/STI including a large Latino, Black/African American, and younger (age 15-24) population but had a lower rate of healthcare providers with prescription authority for home testing kits, which is a requirement under SB 306. Cutting-edge solutions are needed to stem the rising tide of new STI and HIV infections. While SB 306 is novel and innovative in intent, its coverage gaps will increase disparities and inequities among historically underserved populations.